2019
DOI: 10.21203/rs.2.9136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals spatial and temporal turnover of keratinocyte differentiation regulators

Abstract: Background: Keratinocyte differentiation requires intricately coordinated spatiotemporal expression changes that specify epidermis structure and function. Results: This paper utilizes single-cell RNA-seq data from 22,338 human foreskin keratinocytes to reconstruct the transcriptional regulation of skin development and homeostasis genes, organizing them by differentiation stage and also into transcription factor (TF)-associated modules. We identify groups of TFs characterized by coordinate expression changes d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Our results suggest that basal and suprabasal genes could be expressed in the same progenitor cells. It is supported by recent reports that basal and suprabasal genes can be co-expressed during specific stages of keratinocyte differentiation [44,45]. Fourth, we also revealed that calcium level is important for keratinocyte differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…Our results suggest that basal and suprabasal genes could be expressed in the same progenitor cells. It is supported by recent reports that basal and suprabasal genes can be co-expressed during specific stages of keratinocyte differentiation [44,45]. Fourth, we also revealed that calcium level is important for keratinocyte differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…the stratum level, expression patterns of many of the cellular genes are known, but the regulation of spatiotemporal gene expression is a topic of intense investigation (Cavazza et al, 2016;Finnegan et al, 2019;Joost et al, 2016;Klein et al, 2017;Lopez-Pajares et al, 2015;Rubin et al, 2019). Modeling the physiologically relevant tissues will be critical to further our understanding of the viral life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…A prior genomewideassociation study identified ZBED2 as a candidate locus influencing risk of smoking-induced pancreatic cancer (32). More recently, ZBED2 was found to be highly expressed in the basal layer of the epidermis, where it plays a role in regulating keratinocyte differentiation (33). Another study identified ZBED2 as a marker of T cell exhaustion in human CD8 T cells, although the function of ZBED2 was not investigated in this context (34).…”
mentioning
confidence: 99%
“…Notably, we also observe high ZBED2 expression in normal squamous epithelial tissues, such as the skin, lung, and esophageal mucosa, suggesting a normal function for ZBED2 in the regulation of squamous epithelial cells. Interestingly, single-cell RNA-seq analysis recently identified ZBED2 as a key TF in the regulation of human keratinocyte differentiation (33). ZBED2 was predicted to promote the basal state and experimental depletion of ZBED2 was shown to induce keratinocyte differentiation, demonstrated by the up-regulation of KRT10 (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation